Meno autonomija ir demokratija Lietuvos kultūros politikoje - Rimkutė, Audronė (Respectus Philologicus, 2018)
[full article and abstract in Lithuanian; abstract in English]Autonomy of art understood as the independence of the art creation, dissemination and funding organizations from political institutions is one of the most important principles of cultural politics in democratic countries. The idea of artistic autonomy is the basis of the ‘arm’s length’ cultural policy model that works in the United Kingdom and Scandinavian states and which had been ecommended by European Council experts to Lithuania and other Eastern European countries while reforming their cultural policy after the collapse of the Soviet Union. Lithuania finished the transition to the model in 2012-2013 when the Lithuanian Film Centre and the Council for Culture had been established. However, the reaction of Lithuanian political authorities to some of the recent cultural events in Lithuania show that the autonomy of art as an idea and norm of cultural policy has not been working in Lithuania. The aim of this article is to  describe the idea of the autonomy of art in cultural policy and to analyse several actual issues of Lithuanian cultural politics in the aspect of the relationship between the autonomy of art and democracy. The article is based on the analysis of scientific literature, press articles, and political documents.
Keywords: Autonomy of Art, Democracy, Arm’s Length Principle, Lithuanian Cultural Policy, Government of Cultural Organizations